2001
DOI: 10.1159/000056230
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Expressed Emotion and Metabolic Control of Children and Adolescents with Diabetes mellitus

Abstract: Background: The objectives of this study of children and adolescents with diabetes were to: (1) examine whether maternal expressed emotion (EE), in the form of critical comments (CC), hostility and emotional overinvolvement (EOI), is related to metabolic control; (2) determine if CC and EOI are separately related to poor metabolic control, and (3) ascertain whether high EE is related to psychopathology in these children. Methods: The Present Episode version of the Schedule for Affective Disorders and Schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
6
26
0
3
Order By: Relevance
“…The HbA1c levels of adolescents with diabetes in our study were mostly similar to those of other studies (19, 20). We found no association of HbA1c with age and duration of diabetes, and this concurs with other studies (21, 22). In the present study, girls had higher HbA1c levels than boys.…”
Section: Discussionsupporting
confidence: 93%
“…The HbA1c levels of adolescents with diabetes in our study were mostly similar to those of other studies (19, 20). We found no association of HbA1c with age and duration of diabetes, and this concurs with other studies (21, 22). In the present study, girls had higher HbA1c levels than boys.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have consistently found that high family conflict is related to poorer diabetes self-care behaviors and poorer metabolic control, while positive family attributes such as support, warmth, and cohesion are associated with better diabetes self-care behaviors and metabolic control (31,33,108 -110). Data from several studies indicate that parental (predominantly maternal) psychological wellbeing correlates positively with all diabetes metabolic outcomes in their children (i.e., happier mother and better outcomes) (111,112). This finding is similar to a study of patient-perceived family stress in adults by Parkerson et al (113) but is at odds with a more recent study of diabetes-related stress by Stallwood (114).…”
supporting
confidence: 54%
“…The overall effect for psychopathology also was not significant in the initial analyses (see Table 2), but moderator analysis found that the size of the effect varied according to comparison group equivalence. The study with the most equivalent comparison group ([6]; rating of 4) had a negative effect size ( d = −0.35) suggesting that the comparison group had more psychopathology than those with diabetes, and the study with the least equivalent comparison group [54] suggested that those with diabetes had more psychopathology than the comparison group ( d =0.43), with the two studies with mid-level comparison group equivalence (rated 3) reporting effect sizes near 0 ([45], d =0.06; [46]: d =0.12).…”
Section: Resultsmentioning
confidence: 99%